Effect of mulch type on physico-chemical quality of tomato (Solanum lycopersicum) in semi-arid region of India - KANNAUJIA, PANKAJ KUMAR; DUKARE, AJINATH; KALE, SAKHARAM; NATH, PRERNA; SINGH, R K (The Indian Journal of Agricultural Sciences, 2023)
The influence of coloured-plastic mulching on physical and biochemical characteristics of tomato fruits were investigated. During the study, tomato crop was grown in an open field under five coloured-plastic mulching, one organic mulch and a no-mulch treatment. Harvested tomato fruits were analysed for various physico-chemical post-harvest quality parameters. Results evidenced that sphericity of tomatoe fruits was non-significantly (P<0.05) affected by mulching treatment. The highest fruit sphericity (0.96) was observed under yellow mulch followed by black (0.95). Likewise, average fruit weight (57.59 g) and lycopene content (2.99 mg/100 g) was found highest under red mulch. The highest TSS content (4.97) were reported in organic mulch followed by silver (4.90), while ascorbic acid content was highest under white mulch (32.7 mg/100 g) followed by organic mulch (30.9 mg/100g). Under black mulch, the highest levels of phenolic content (59.0 μg GAE/100 g) as well as antioxidant activity (10.50 μmol TE/g) were observed. Overall results showed that black mulch performed better, followed by red and white plastic mulch treatments.